Implementation Of The Nature Of Science And Social Sciences In The World Of Education - Sahbuki Ritonga; Zulpahri Nainggolan; Soybatul Aslamiah Ritonga3; Raden Sri Ayu Ramadhana; Muhammad Fauzi Romadhon Marpaung; Wahyu Azhar Ritonga (CV. AFDIFAL MAJU BERKAH, 2022)
Implimentation of the nature of science and social science in the world of education aims to form a mindset and mindset of feeling towards students who are more consistent in learning so that education is realized that gives birth to future generations with a scientific mindset, with concepts, principles, theories and emotional and social intelligence in each individual student. The method of theoretical studies and observations in schools that science and social sciences cannot be separated from the learning process in the world of education, from the results of data testing that we have carried out that social phenomena are always related to their environment. Implementation of the nature of science and social science in the world of education that there are vibrations and energy waves to carry out an activity in learning which essentially already exists in each individual. Data processing results using spss for windows obtained Fhitung=13.618 with sig. 0.000 and Fhitung= 8.385 with sig.0.001 from for Ftable= 3.19 the results obtained in relation to the implementation is very significant.